Theoretical and methodological basis of fare system management in public transport - Sokol, K. M.; Stamatin, O. V.; Sukhonos, M. K.; Lahunova, I. A.; Medvedchuk, O. V. (ASERS Publishing, Romania, 2019)
The research paper considers the issues of ensuring effective management of the processes of transformation of fare systems in public transport. Were analyzed the prospects for implementation of automated fare control systems and also the theoretical and methodological approaches to the formation of existing automated fare systems, which could determine the perspective of implementation of such systems in the domestic market of transport services provision, that can solve a number of problems related with fare simplicity and comfort, formation of a flexible fare system, use of various forms of payment, as well as monitoring and control of money revenues, including for transportation of preferential contingent.
Keywords: automated control systems; fare; control mechanisms; economic and mathematical modeling; public transport